COVID-19 Lockdowns and Decline in Traffic Related Deaths and Injuries - Umut Oguzoglu (Institute of Labor Economics (IZA), 2020)
This paper investigates the decline in traffic accidents, fatalities and injuries during the months that COVID-19 stay-at-home orders implemented in Turkey. Taking into account the decline in accidents in March and April together, these rates roughly translate to 200 traffic related deaths and 17,600 injuries avoided during the months that stay-at-home orders were in place. The Difference in Difference estimates that exploit variation in quarantine orders among small cities, I also show that stricter rules in April are responsible for the decline of accidents with death or injury by 35 percent, death by 72 percent and injuries by 19 percent.
Keywords: P48; Q53; Q58; 330; COVID-19; safer-at-home; lockdowns; traffic accidents; fatality; injury; Turkey